1986
DOI: 10.2214/ajr.147.4.705
|View full text |Cite
|
Sign up to set email alerts
|

CT of appendicitis

Abstract: The CT findings of 38 consecutive patients with acute appendicitis are analyzed, described, and illustrated. CT showed intraabdominal disease in 92% of patients and made a specific diagnosis of appendicitis in 79% of cases. The most common CT findings were pericecal inflammation (68%), abscess (55%), calcified appendicolith (23%), and an abnormal appendix (18%). CT had a sensitivity similar to that of contrast enema examinations, but it correlated much better with the surgical findings in detecting the precise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…Computed tomography of the abdomen and pelvis (CT-A/P) has become the diagnostic modality of choice for evaluation of acute right lower quadrant abdominal pain [1][2][3]. CT-A/P has become an important diagnostic tool to diagnose or exclude acute appendicitis, with a sensitivity and negative predictive value that surpasses compression sonography and clinical exam [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography of the abdomen and pelvis (CT-A/P) has become the diagnostic modality of choice for evaluation of acute right lower quadrant abdominal pain [1][2][3]. CT-A/P has become an important diagnostic tool to diagnose or exclude acute appendicitis, with a sensitivity and negative predictive value that surpasses compression sonography and clinical exam [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…13 His initial study of 60 patients reported ultrasound had a sensitivity of 89%, a specificity of 100% and an overall accuracy of 95%. Later that year, Balthazar and colleagues 14 reported results from a series of 38 patients with proven appendicitis, 30 of whom were accurately diagnosed on CT, resulting in a sensitivity of 79%. Over the next 20 years, dozens of studies evaluated various aspects of each of these modalities and their perceived benefits and shortcomings, but only a few were specific to children.…”
mentioning
confidence: 99%
“…The present study was done to evaluate the use of Modified Alvarado scoring system in reducing the number of negative appendicectomy and to evaluate the sensitivity of MASS in diagnosis of Acute Appendicitis.Our results and observations were discussed and compared with various studies. The age group in which acute appendicitis occurred commonly was between 12 and 30 years [10]. The result of present study showed that a high score (> 7) in men was a satisfactory aid in early diagnosis of acute appendicitis , the overall sensitivity in men with scores > 7 was 91.30% .…”
Section: Discussionmentioning
confidence: 48%